2014
DOI: 10.1111/cea.12409
|View full text |Cite
|
Sign up to set email alerts
|

Early risk factors for pubertal asthma

Abstract: Important early risk factors for pubertal asthma were early airways obstruction, parental rhinitis, being the firstborn child, and perinatal familial stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 56 publications
(104 reference statements)
2
20
0
Order By: Relevance
“…These results were supported by others studies showing that early severe LRTIs are associated with up to a four‐fold risk of subsequent wheezing during early school years . In addition the number and severity of early life bronchial obstructive episodes has been shown to have the greatest impact on risk of pubertal asthma . Recent research from Copenhagen Prospective Studies on Asthma in Childhood revealed that otherwise healthy children experienced a median of 10 episodes of respiratory tract infections (one episode per child for LRTIs) during the first three years of life .…”
Section: Discussionsupporting
confidence: 56%
“…These results were supported by others studies showing that early severe LRTIs are associated with up to a four‐fold risk of subsequent wheezing during early school years . In addition the number and severity of early life bronchial obstructive episodes has been shown to have the greatest impact on risk of pubertal asthma . Recent research from Copenhagen Prospective Studies on Asthma in Childhood revealed that otherwise healthy children experienced a median of 10 episodes of respiratory tract infections (one episode per child for LRTIs) during the first three years of life .…”
Section: Discussionsupporting
confidence: 56%
“…A total of 20 studies were chosen:345678910111213141516171819202122 17 prospective cohort studies 3456891011121314151819202122 and 3 national registry studies 71617. Most studies used general population samples, although not all were nationally representative.…”
Section: Evidence Of the Impact Of Prenatal Maternal Distress On Allementioning
confidence: 99%
“…Most studies used general population samples, although not all were nationally representative. Prenatal maternal distress had a close association with wheezing/asthma in 17 studies346789101112131415161718192122 and atopic dermatitis in 5 studies 511122022. Two studies reported good relationships with both asthma and atopic dermatitis 1122.…”
Section: Evidence Of the Impact Of Prenatal Maternal Distress On Allementioning
confidence: 99%
“…Puberty and adolescence were featured by asthma in puberty (Hovland et al. ) and incident wheezing and asthma in adolescence (Hedman et al. ).…”
Section: Asthma and Rhinitismentioning
confidence: 99%